PENGARUH KEMANDIRIAN BELAJAR, EFIKASI DIRI DAN KESADARAN METAKOGNISI TERHADAP HASIL BELAJAR KIMIA PESERTA DIDIK KELAS XI KURIKULUM MERDEKA SMAN 8 MAKASSAR - Indira Magfirah; Muhammad Anwar; Halimah Husain (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aimed to examine the contribution of self-regulated learning, self-efficacy, and metacognitive awareness to chemistry learning outcomes among eleventh-grade Merdeka students at SMAN 8 Makassar. A correlational ex post facto design with a quantitative approach guided the research process. The sample was determined using saturated sampling, involving the entire population of 188 students from six classes. Data were collected through two instruments: a Likert-scale questionnaire to measure the three predictor variables and a 15-item chemistry achievement test on thermochemistry. Both instruments underwent validity testing using product moment correlation and reliability testing using Cronbach's Alpha, both confirming valid and reliable results. Data were analyzed using descriptive statistics and multiple linear regression processed through SPSS version 27. Findings revealed that the three variables simultaneously had a significant effect on students' chemistry learning outcomes (F = 66.368; p < 0.001). Partially, metacognitive awareness emerged as the strongest predictor (β = 0.393; p < 0.001), followed by self-regulated learning (β = 0.212; p = 0.005) and self-efficacy (β = 0.190; p = 0.024). The R² value of 0.520 indicated that the three variables jointly explained 52% of the variance in chemistry learning outcomes. This study was limited to eleventh-grade students at a single school, so generalization should be made cautiously. These findings affirm the importance of instructional design that fosters self-regulated learning, strengthens self-efficacy through constructive feedback, and embeds metacognitive strategy training to support sustainable improvement in chemistry learning outcomes. ABSTRAK Penelitian ini bertujuan mengkaji kontribusi kemandirian belajar, efikasi diri, dan kesadaran metakognisi terhadap hasil belajar kimia peserta didik kelas XI Merdeka di SMAN 8 Makassar. Desain ex post facto korelasional dengan pendekatan kuantitatif digunakan dalam penelitian ini. Sampel ditetapkan melalui teknik sampling jenuh, melibatkan seluruh populasi sebanyak 188 peserta didik dari enam rombongan belajar. Data dikumpulkan menggunakan kuesioner Likert untuk mengukur ketiga variabel prediktor dan tes hasil belajar kimia pada materi termokimia sebanyak 15 butir, yang telah diuji validitas (korelasi product moment) dan reliabilitas (Cronbach's Alpha) dengan hasil valid dan reliabel. Analisis data menggunakan statistik deskriptif dan regresi linier berganda melalui SPSS versi 27. Hasil menunjukkan ketiga variabel secara simultan berpengaruh signifikan terhadap hasil belajar kimia (F = 66,368; p < 0,001). Secara parsial, kesadaran metakognisi menjadi prediktor terkuat (β = 0,393; p < 0,001), diikuti kemandirian belajar (β = 0,212; p = 0,005) dan efikasi diri (β = 0,190; p = 0,024). Nilai R² = 0,520 menunjukkan ketiga variabel menjelaskan 52% variasi hasil belajar kimia. Penelitian terbatas pada peserta didik kelas XI satu sekolah sehingga generalisasi perlu dilakukan secara hati-hati. Temuan ini menegaskan pentingnya pembelajaran yang menumbuhkan kemandirian belajar, memperkuat efikasi diri melalui umpan balik konstruktif, dan melatih strategi metakognisi untuk meningkatkan hasil belajar kimia berkelanjutan.